2017
DOI: 10.1177/1758573217701065
|View full text |Cite
|
Sign up to set email alerts
|

The effect of humeral polyethylene insert constraint on reverse shoulder arthroplasty biomechanics

Abstract: Altering polyethylene cup constraint in RSA to enhance stability does not significantly alter resultant joint loads and deltoid forces. Surprisingly, terminal abduction range of motion was also not significantly different with varying cup constraint, indicating that terminal impingement may be tuberosity related rather than polyethylene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“… 130 Lastly, humeral socket depth defined in ratio to glenosphere diameter will increase stability at the potential cost of a reduced range of motion. 139 , 144 , 152 …”
Section: Reverse Shoulder Arthroplastymentioning
confidence: 99%
“… 130 Lastly, humeral socket depth defined in ratio to glenosphere diameter will increase stability at the potential cost of a reduced range of motion. 139 , 144 , 152 …”
Section: Reverse Shoulder Arthroplastymentioning
confidence: 99%
“…Finally, he concluded when the constraint joint was implanted to improve the joint stability, joint load and deltoid forces during active abduction were not affected signi cantly. Simultaneously, the range of motion was also not signi cantly different from that of a conventional reverse shoulder [21].…”
Section: Discussionmentioning
confidence: 75%
“…The authors concluded that polyethylene constraint had limited effect on RTSA kinematics. 1 It should be noted, however, that biomechanical studies primarily evaluate glenohumeral motion, while clinically, motion after RTSA involves both glenohumeral and scapulothoracic motion, so these biomechanical findings may not translate directly to what is observed clinically.…”
Section: Discussionmentioning
confidence: 99%